2019
DOI: 10.1016/j.molliq.2019.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium surfactants derived from leucine and methionine: Novel challenging surface active molecules with antimicrobial activity

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…The cytotoxicity of the N -benzyl quaternary ammonium surfactants derived from leucine in comparison to the commercial BAC was studied by performing two cytotoxicity assays (MTS and LDH as indicators of metabolic activity and membrane integrity, respectively) and by a haemolytic assay. The assays were conducted as reported in our previous publications [5,14]. EC 50 values from the MTS assay (concentration of surfactant that causes 50% cell death) and the LDH assay (concentration of surfactants that causes 50% LDH release from cells), as well as HC 50 values from the haemolytic assay (concentration of surfactants that causes 50% haemoglobin release from erythrocytes) were calculated using a nonlinear regression model (Prism version 5.0, GraphPad Inc., San Diego, CA, USA) as follows:Y=BOTTOM+TopBottom1+10(LogEC50normalx) Hill Slope where Top and Bottom are plateaux in the units of the Y axis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of the N -benzyl quaternary ammonium surfactants derived from leucine in comparison to the commercial BAC was studied by performing two cytotoxicity assays (MTS and LDH as indicators of metabolic activity and membrane integrity, respectively) and by a haemolytic assay. The assays were conducted as reported in our previous publications [5,14]. EC 50 values from the MTS assay (concentration of surfactant that causes 50% cell death) and the LDH assay (concentration of surfactants that causes 50% LDH release from cells), as well as HC 50 values from the haemolytic assay (concentration of surfactants that causes 50% haemoglobin release from erythrocytes) were calculated using a nonlinear regression model (Prism version 5.0, GraphPad Inc., San Diego, CA, USA) as follows:Y=BOTTOM+TopBottom1+10(LogEC50normalx) Hill Slope where Top and Bottom are plateaux in the units of the Y axis.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper, we synthesised and characterised the surface activity, cytotoxicity, and antimicrobial properties of two series of linear quaternary ammonium compounds, based on the amino acid leucine and methionine and with different hydrophobic chain lengths (C10, C12 and C14). These amphiphiles, especially derivatives with a C12 and C14 hydrocarbon chain, showed a satisfactory cytotoxicity and an antibacterial profile that was comparable to benzalkonium chloride (BAC), with higher activity observed against Gram-positive bacteria [14]. In the present work, we report the synthesis of the same series of leucine-based surfactants by introducing an N -benzyl group, which is a common substituent of commercial quaternary ammonium compounds (e.g., benzalkonium chloride).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the most numerous groups of compounds used as chemical inhibitors of biocorrosion are nitrogen compounds, including aliphatic amines such as N-(3-aminopropyl) -N-dodecylpropane 1,3-diamine and quaternary alkylammonium salts such as chloride didecyldimethylammonium [79]. Based on the literature [80,81] it is well-known that biocidal preparations containing quaternary alkylammonium salts or the newest quaternary ammonium surfactants [81], as active substances, are effective in limiting fungal population and cause no damage or physical changes on disinfected surfaces. Adsorption of these compounds on inanimate surfaces cause removal of water molecules and forming a monomolecular protective salt layer of alkylammonium, which protects the material against corrosion in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of these compounds on inanimate surfaces cause removal of water molecules and forming a monomolecular protective salt layer of alkylammonium, which protects the material against corrosion in the future. Quaternary alkylammonium salts are not reactive, which is why they adsorb on surfaces and do not induce any chemical reactions [80,81]. Considering the above, it was strongly recommended to use preparation from this group in the studied cave.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In another study, the antimicrobial activity of leucine- and methionine-based esters was shown against bacteria and yeast. 14 Encouraged by these results, we synthesized arginine esters with C 18 and C 24 carbon chains, namely, arginine-oleate and arginine-decyltetradecanoate esters (Arg-OL and Arg-DT). Oleyl alcohol was chosen because of its monounsaturated hydrophobic tail, providing a comparatively bulky lipophilic group, and 2-decyl-1-tetradecanol was chosen because of its branched lipophilic structure.…”
Section: Introductionmentioning
confidence: 99%